NON GOVERNMENTAL ORGANIZATIONS AND THEIR ROLES IN PROMOTING SUSTAINABLE AGRICULTURE AND RURAL DEVELOPMENT IN CAMEROON - ELIBE BRUNO, Ekale (The Graduate School, Ajou University, 2011)
Cocoa is one of the most important cash crops in Cameroon. Its production plays a very important role in the economy of rural communities of the country with a production rate representing about 37% of the total cultivable land of the country. But sustainability of cocoa production still remains a big issue. Some scholars attribute the alleged decline in cocoa quality and the production system to be associated with the dangers of Economic liberalization which came up as a result of the structural adjustment reforms set up by the World Bank and IMF in developing countries. Others attribute this decline to the lack of proper management and control by the government and other market institutions. This study looks at this problem to be associated with the neglect of NGO roles in promoting sustainable cocoa production. The research thus seek to analyze the changing challenges that NGOs are facing in these communities and brings out some good practices for NGO interventions. Encouraging the intensification of cocoa production and bringing up good policies to promote its marketing is necessary for reducing rural poverty and promote sustainable rural development as cocoa production offers a significant opportunity for poverty alleviation
학위논문(석사)--아주대학교 국제대학원--NGO학과,2011. 2
Keywords: MY DESSERTATION SUBMISSION